2009
DOI: 10.1152/ajpregu.90902.2008
|View full text |Cite
|
Sign up to set email alerts
|

MitoQ administration prevents endotoxin-induced cardiac dysfunction

Abstract: Sepsis elicits severe alterations in cardiac function, impairing cardiac mitochondrial and pressure-generating capacity. Currently, there are no therapies to prevent sepsis-induced cardiac dysfunction. We tested the hypothesis that administration of a mitochondrially targeted antioxidant, 10-(6'-ubiquinonyl)-decyltriphenylphosphonium (MitoQ), would prevent endotoxin-induced reductions in cardiac mitochondrial and contractile function. Studies were performed on adult rodents (n = 52) given either saline, endoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 31 publications
2
119
0
1
Order By: Relevance
“…Protecting complex I and II activity is important because these complexes initiate oxidative phosphorylation and can generate additional oxidants once inactivated. MitoQ has been shown to restore mitochondrial function in a rodent model of cardiac dysfunction induced by sepsis (Supinski et al, 2009). Those authors previously determined that cardiac mitochondrial dysfunction in this model was associated with a significant increase in ROS generation.…”
Section: Discussionmentioning
confidence: 98%
“…Protecting complex I and II activity is important because these complexes initiate oxidative phosphorylation and can generate additional oxidants once inactivated. MitoQ has been shown to restore mitochondrial function in a rodent model of cardiac dysfunction induced by sepsis (Supinski et al, 2009). Those authors previously determined that cardiac mitochondrial dysfunction in this model was associated with a significant increase in ROS generation.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the development of antioxidant molecules that achieve concentrations in mitochondria 100-to 1,000-fold higher than in the cytosol, such as Szeto-Schiller (SS) synthetic antioxidant peptides (26,178,179,230), MitoQ (176,205), and Euk-8 (a SOD/catalase mimetic and antioxidant) (94,202), have demonstrated some efficacy in models of cardiovascular stress. A recent study in spontaneous hypertensive rats showed that MitoQ treatment for 8 weeks significantly reduced systolic blood pressure, improved endothelial function, and attenuated cardiac hypertrophy (64).…”
Section: Mitochondrial Dysfunction As a Pharmacological Target Againsmentioning
confidence: 99%
“…Although it is unclear whether mitochondria play a causative role in the pathology of neurodegenerative diseases, aging, and carcinogenesis, mitochondria-targeted antioxidants have been shown to be potent at sequestering reactive oxygen intermediates 80,81,93 . The use of mitochondrialtargeted antioxidants is a step toward understanding whether antioxidants can be efficient preventive or therapeutic tools against age-related diseases.…”
Section: Levels Of Antioxidant Actionmentioning
confidence: 99%